Strategic Disclosure of Risky Prospects: A Laboratory Experiment - Hobson, Jessen L.; Kachelmeier, Steven J. (The Accounting Review, 2005)
In a market experiment, buyers respond to sellers' disclosures of one of the two potential outcomes of a risky prospect. Buyer reactions reflect two separate disclosure phenomena that heretofore have not been considered jointly. First, consistent with cognitive predictions that users tend to anchor on explicit one-sided disclosures, buyers pay more relative to expected value when the seller discloses the higher of the two potential outcomes than when the seller discloses the lower potential outcome. Second, consistent with the incentive-driven predictions of information economics, buyers systematically discount bids when sellers choose which potential outcome they wish to disclose, relative to bids in a control condition in which the seller is constrained to disclose randomly. Both findings are robust to each other, addressing qualifications in prior research about generalizing cognitive disclosure phenomena to a strategic disclosure environment. One implication supported by the data is that if cognitive information processing limitations are robust to a strategic environment, then strategic agents can exploit these limitations when choosing disclosures.